Ideas: Time to go out and play - Hayley Christian (The UNESCO Courier, 2023)
Children occupying public places is a common theme in early 20th century street photography: they carry loads, wear backpacks to school, run around, float paper boats in Parisian gutters, or play in water sprayed from fire hydrants in New York – without an adult in sight. Nowadays, it’s hard to get such shots. The sight of young children playing, walking or cycling in public places without adult supervision has become rare.